Shear Bond Strength of Rebonded Ceramic Brackets Using Four Different Methods of Adhesive Removal - AmirHossein Mirhashemi; Mohammad Hashem Hosseini; Nasim Chiniforoush; Armin Soudi; Meisam Moradi (Tehran University of Medical Sciences, 2018)
Objectives: Rebonding of isolated brackets is an economic option that can be conducted using available in-office or commercial recycling methods. Nowadays, lasers are known as an efficient modality for composite removal, but there is not much information available about using lasers for removal of adhesive remnants from the ceramic bracket base. Materials and Methods: Fifty human premolar teeth were divided into five groups. Samples in all groups were bonded to ceramic brackets. Brackets in four groups were debonded and the remaining adhesive was removed by Er:YAG laser, Er;Cr:YSGG laser, sandblasting or direct flame. After removing adhesives from the tooth surfaces by carbide bur, the recycled brackets were bonded again. in the control group, new ceramic brackets were bonded.  Finally, all brackets were debonded by universal testing machine and their shear bond strength (SBS) was measured. The adhesive remnant index (ARI) was calculated under a stereomicroscope at x10 magnification. Data were analyzed using one-way ANOVA and Tukey's test. Results: SRS values showed no significant difference among the five groups (P=0.568). The highest SRS was noted in the control group (7.46±1.4 MPa), followed by Er:YAG laser group (7.40±1.24 Mpa) and the lowest was noted in the flame group (6.32±2.3 Mpa). ARI scores indicated that most of the adhesive remained on the tooth surface in all groups Conclusions: Recycling of ceramic brackets with Er:YAG laser is an efficient in-office method which causes the least damage to the bracket base. However, all methods of bracket recycling showed acceptable SBS.